2014
DOI: 10.4049/jimmunol.1400648
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activation by Campylobacterjejuni

Abstract: The Gram-negative pathogen Campylobacter jejuni is the most common cause of bacterial foodborne disease worldwide. The mechanisms that lead to bacterial invasion of eukaryotic cells and massive intestinal inflammation are still unknown. In this study, we report that C. jejuni infection of mouse macrophages induces upregulation of pro–IL-1β transcript and secretion of IL-1β without eliciting cell death. Immunoblotting indicated cleavage of caspase-1 and IL-1β in infected cells. In bone marrow–derived macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Given that C. concisus UNSWCD does not have a classical type III secretion system (its flagellum acts as a type III export system) or a type IV secretion system (21), it is possible that NLRC4 is not a major sensor of C. concisus infection. Our results for NLRP3 and NLRC4 are in line with the recent findings of Bouwman and colleagues showing that IL-1B secretion following C. jejuni infection was dependent on invasion-related activation of the NLRP3 inflammasome and not NLRC4 (35). Of the other genes encoding CARD-containing members within the NLR family, NLRC5, encoding a potential regulator of interferon signaling and production of major histocompatibility complex (MHC) class I molecules (36)(37)(38), was upregulated upon infection with C. concisus (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 82%
“…Given that C. concisus UNSWCD does not have a classical type III secretion system (its flagellum acts as a type III export system) or a type IV secretion system (21), it is possible that NLRC4 is not a major sensor of C. concisus infection. Our results for NLRP3 and NLRC4 are in line with the recent findings of Bouwman and colleagues showing that IL-1B secretion following C. jejuni infection was dependent on invasion-related activation of the NLRP3 inflammasome and not NLRC4 (35). Of the other genes encoding CARD-containing members within the NLR family, NLRC5, encoding a potential regulator of interferon signaling and production of major histocompatibility complex (MHC) class I molecules (36)(37)(38), was upregulated upon infection with C. concisus (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 82%
“…In addition, some bacteria have been implicated in activation of the NLRP3 inflammasome [ 54 , 55 ]. For example, Campylobacter jejuni could activate NLRP3 inflammasome and induce IL-1β secretion in mouse macrophages without eliciting cell death [ 56 ]. Our lab has previously demonstrated that the expression of NLRP3 is stimulated in piglet mononuclear phagocytes induced by LPS and baicalin could inhibit the NLRP3 inflammasome expression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA synthesis was carried out by iScript cDNA Synthesis Kit (170-8891; Bio-Rad, Hercules, CA) as per the manufacturer's instructions. Primer sequences for various genes amplified were as described in Bouwman et al 56 Reactions were performed in Roche Light Cycler 480 Real-time PCR system under the following conditions: 94 1C/2 min for 1 cycle; 94 1C/30 s, 50 1C/30 s, 72 1C/60 s for 40 cycles; 72 1C/7 min for 1 cycle.…”
Section: Methodsmentioning
confidence: 99%